Process Capabilitiy Of Tin Plating Inspection : A Case Study - Mohamad, Siti Nurul Hazlina (2019)
This project begins with an industrial visit to industry selected that is XYZ Sdn. Bhd, Pasir Gudang, focused at production site and inspection area. This industrial attachment is very helpful in achieving objective study because the work done involves coating weight inspection. This case study was concerning on process capability of tin plating inspection. In plating industry, the most popular option for coating is of tin plating. This option is popular because it is more economical and does not require high costs in manufacturing. Due to the characteristic properties of tin plating having good corrosion resistance, ductility, and reliability, it is widely used in various industries including buildings, food, electricity and electronics, heavy industries and oil and gas. There are issues that having problem on the business which is in the last few months, this company has found a lot of complaints and rejects from customers regarding its product related to tin coating. The specification of the product is on request from the customer but in this case, the customer has set a guarantee limit called the Lower Specification Limit value of 2.45 m / g2 the Upper Specification Limit is not more than 3.0 m / g2. The customer has placed the most accurate capability index for a certain parameter which is coating weight was at least 1.33. However, it is still meet the customer’s specification and acceptable if the index capability value is not less than 1.00. Therefore, this company has requested the inspection division to state whether a customer-ordered product meets the needs of the customer or not by proving through process capability. From the inspection process, the sample of data has been collected. Due to that situation, main focus of this study is to investigate whether the product produced by the company meet the customer’s specification their capability index for a certain parameter which is coating weight was at least 1.33 using process capability study. Process capabilities is an increasingly popular method used by many of today's industry to see the capability of a process or the quality of a product.In the process of achieving the main objectives which is to determine the optimum parameters of coating process, hypothesis testing has been done. The other purposed of this for this case is to study the element of tin plating process and also to study about coating inspection process and tools. The success of an organization or company depends on a high quality product and meets customer requirements. All the sample data collected from inspection process has been recorded in MS Excel and analyzed using MINITAB software.